Rocking Lockdown Raya / Dr. Ratna Zuarni Ramli and Mazliyana Zainal Arifin - Ramli, Ratna Zuarni; Zainal Arifin, Mazliyana (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
It is time to enjoy a brand new Raya vibes safely at home. While Zoom and Meet sound a bit mainstream, one can connect to the beloved family through social media apps that enable them to connect with 6 (IG call), 8 (WA call) or even 32 (Facetime) people at a time! Willing to try locally made food delivery apps? Log on to Mammam or Dah Makan. Though food choices are not as varied as Food Panda or Grab, it is worth a try! MizzNina vs Neelofa? QalbyApp vs TheNoor? Both are great and the best is You and the Quran berpisah tiada cia cia cia. NO serious work on raya? Empower your digital skills (online communication, digital media handling, online creativity), by uploading your 30secs TikTok or Reel video and understand the limit of its security and safety. Be bold be fun!